Effect of swimming on bone metabolism in adolescents - Derman, Orhan; Cinemre, Alphan; Kanbur, Nuray; Doğan, Muhsin; Kiliç, Mustafa; Karaduman, Erdem (The Turkish Journal of Pediatrics, 2008)
Physical activity has been shown to have a positive effect on bone metabolism among adolescents. The objective of this study was to determine the effect of swimming on bone metabolism during adolescence. Swimming, as a non-weight-bearing sport, has been considered to be insignificant in the maintenance of bone mass. We studied whether swimming is associated with a higher peak bone mass. Forty swimmers (males aged 10-17 years and females aged 9-16 years) were studied. The control group consisted of the same number of adolescents aged between 10-16 years who did not swim; distribution of male and female gender was similar in the non-swimming control group compared to the swimming group. Adolescents were matched for age, gender and pubertal stages based on Tanner staging. All subjects underwent combined measurement of bone mineral metabolism by dual-energy X-ray absorptiometry of total body calcium content, and specific biochemical markers of turnover including osteocalcin, calcium, phosphorus and alkaline phosphatase. Bone age (determined by Greulich and Pyle’s Radiographic Atlas of Skeletal Development of the Hand and Wrist), weight, height, ideal body weight, ideal body weight ratio, body mass index, Tanner classification (rated by examiner), diet, history of tobacco and alcohol exposure, exercise, socioeconomic status and history of chronic illness and medications were recorded to evaluate potential mediators that would affect bone metabolism. Tanner staging was used to assess puberty, and diet was evaluated based on reported consumption of milk, yogurt and cheese and cola/caffeine beverage consumption daily. There was significant difference in bone mineral content between adolescent male swimmers and the control group males. Consumption of cola beverages were significantly higher among the control group compared with the swimmer group. Ideal body weight ratio was significantly high among the female control group compared with female swimmers. Milk consumption was significantly higher for both male and female swimmer groups, whereas yogurt consumption was only significantly higher in the male swimmer group compared with control group. These results indicate that a highly active nonimpact sport such as swimming may lead to increased bone mineral content only for male swimmers. However, dietary behaviors may be more important than swimming on bone metabolism among adolescents.